(3QSGdI aj GdaQGSIs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3GdMeO ddg def jSJMb GdMeO dghjJgagPg QSGdI eTJedI Ydi eYGf bdjdI ef Yde GdaQGSI s
(3BNQgG (B:s
(3JfJgi CKfGA GdcdGe Ydi CTcGd GdTaI hGdae hGdCSfGf s
(3jdGMX Cfg jhLO ai gPG GdagQS KdGK QSGFd ai GdaQGSI ddaGQGHi hdTjN GdQHhI hddaNQ GdQGRi hcdgG QSGdI hGMOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGdQa YGeI (B- (3U (B141 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdaQGSIs